Cigarette smoke induces direct DNA damage in the human B-lymphoid cell line Raji - Yang, Qin; Bartsch, Helmut (Carcinogenesis, 1999)
Human lymphoid cells (Raji) were exposed to water-soluble compounds from cigarette smoke (CS) generated in a smoking machine. DNA damage, as detected by alkaline single-cell microelectrophoresis (COMET assay), was induced in a time- and concentration-dependent manner in the cells. Most of the rapidly induced DNA damage was attributable to direct-acting compounds since cytochrome P450-related metabolic activities (ethoxy- and pentoxyresorufin-O-deethylases and coumarin-7-hydroxylase) were absent or very low. In addition, induction of DNA damage could be inhibited only slightly by β-naphthoflavone and coumarin. Vitamin C enhanced DNA damage in Raji cells probably by redox cycling of catechol and hydroquinone present in CS implicating reactive oxygen intermediates as another source of DNA damage. N-acetylcysteine, a radical scavenger and glutathione precursor, reduced DNA damage in Raji cells when exposure to CS was followed by 2 h post-incubation in culture medium. Unrepaired DNA damage caused by CS persisted longer than γ-irradiation-induced DNA damage. Among the CS constituents, acrolein, but not formaldehyde and acetaldehyde, induced DNA damage although less intensely than CS itself. At 50 and 100 μM concentrations, acrolein also inhibited repair of γ- irradiation-induced DNA damage in the COMET assay. Inhibition of DNA synthesis by acrolein at 50 μM was demonstrated by an immunochemical assay for bromo-deoxyuridine incorporation; however, inhibition of a representative repair enzyme, 8-oxoguanosine hydrolase, by either CS or acrolein was not observed. The present results further confirm the presence of direct-acting genotoxic components and inhibitors of DNA repair in the gas phase of tobacco smoke, that may contribute to DNA damage and smoking-associated cancers of the upper aerodigestive tract.